Patient-identified information and communication needs in the context of major trauma - Sandra Braaf; Shanthi Ameratunga; Andrew Nunn; Nicola Christie; Warwick Teague; Rodney Judson; Belinda J. Gabbe (BMC, 2018)
Abstract Background Navigating complex health care systems during the multiple phases of recovery following major trauma entails many challenges for injured patients. Patients' experiences communicating with health professionals are of particular importance in this context. The aim of this study was to explore seriously injured patients' perceptions of communication with and information provided by health professionals in their first 3-years following injury. Methods A qualitative study designed was used, nested within a population-based longitudinal cohort study. Semi-structured telephone interviews were undertaken with 65 major trauma patients, aged 17 years and older at the time of injury, identified through purposive sampling from the Victorian State Trauma Registry. A detailed thematic analysis was undertaken using a framework approach. Results Many seriously injured patients faced barriers to communication with health professionals in the hospital, rehabilitation and in the community settings. Key themes related to limited contact with health professionals, insufficient information provision, and challenges with information coordination. Communication difficulties were particularly apparent when many health professionals were involved in patient care, or when patients transitioned from hospital to rehabilitation or to the community. Difficulties in patient-health professional engagement compromised communication and exchange of information particularly at transitions of care, e.g., discharge from hospital. Conversely, positive attributes displayed by health professionals such as active discussion, clear language, listening and an empathetic manner, all facilitated effective communication. Most patients preferred communication consistent with patient-centred approaches, and the use of multiple modes to communicate information. Conclusions The communication and information needs of seriously injured patients were inconsistently met over the course of their recovery continuum. To assist patients along their recovery trajectories, patient-centred communication approaches and considerations for environmental and patients' health literacy are recommended. Additionally, assistance with information coordination and comprehensive multimodal information provision should be available for injured patients.